Training & Development, Organizational Commitment and Turnover Intentions in Financial Sector Moderating Role of Constituent Attachment - Fakhare Alam Siddiqui; Hammad Zafar; Fizra Javed (Indus Journal of Social Sciences, 2025)
This paper examines how training and development leads to an impact on employees’ intention to leave in the financial sector, with commitment to the organization as a mediating variable and constituent attachment as a moderating variable whereas training availability, learning motivation, and manager’s support for training play roles as independent variables. A quantitative strategy was employed, using a survey form to get information from a random stratified sample of financial sector employees. Smart PLS was employed to analyse data., and SPSS for demographic analysis. Three hundred surveys were sent out, and seventy percent of them were returned.(n = 210) out of which only 204 responses were valid. The findings indicate that training and development and motivation to learn don’t have any influence on turnover intentions, with organizational commitment mediating this relationship. Constituent attachment doesn’t moderates The relationship between organisational commitment and intention to leave whereas only managerial support for training significantly influence turnover intention. The findings suggest that financial sector organizations can reduce turnover intentions by investing in training and development, fostering commitment to the organization, and promoting constituent attachment.